2019
DOI: 10.1002/er.5051
|View full text |Cite
|
Sign up to set email alerts
|

Synthesised spirobichroman‐based polyimide functionalized by pyridine: Effects of substituent position on gas separation and thermal properties

Abstract: Summary Spirobichroman‐based polymers have garnered considerable attention as promising gas separation membrane materials. Herein, two spirobichroman‐based diamines were synthesised using a pyridine heterocyclic ring with methyl substituents at different positions. The diamines were reacted with 4,4′‐(hexafluoroisopropylidene)diphthalic anhydride (6FDA) and bis‐(3‐phthalyl anhydride) ether (ODPA) to achieve four polyimides functionalised by pyridine. The polymers performances were characterised by experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Following are the reasons for the high solubility of the polymer: (i) the spirobichroman-based structure and the presence of large bulky -C(CF 3 ) 2groups increased the noncoplanarity of the molecule and reduced the density of the polymer packing; (ii) an electron-decient heterocyclic pyridine unit was incorporated into the polymer, enhancing the dipole-dipole interaction between the polymer and solvent, thus increasing polymer solubility; and (iii) the ether bond is considered to increase the movement of chain segments and enhance the solubility of the polymer in organic solvents. [37][38][39] Furthermore, the morphology of the synthesised PIs was investigated through WAXD analysis. The results are shown in Fig.…”
Section: Solubility and Morphology Of Pismentioning
confidence: 99%
“…Following are the reasons for the high solubility of the polymer: (i) the spirobichroman-based structure and the presence of large bulky -C(CF 3 ) 2groups increased the noncoplanarity of the molecule and reduced the density of the polymer packing; (ii) an electron-decient heterocyclic pyridine unit was incorporated into the polymer, enhancing the dipole-dipole interaction between the polymer and solvent, thus increasing polymer solubility; and (iii) the ether bond is considered to increase the movement of chain segments and enhance the solubility of the polymer in organic solvents. [37][38][39] Furthermore, the morphology of the synthesised PIs was investigated through WAXD analysis. The results are shown in Fig.…”
Section: Solubility and Morphology Of Pismentioning
confidence: 99%
“…15,16,[19][20][21][22] Yeong et al 23 designed CARDO-copolybenzoxazole through thermally induced structural rearrangement, and the results showed that threefold increase in CO 2 permeability compared to the noncardo counterparts. Wang et al 24 synthesized polyimides containing pyridine heterocycles with basic groups, which had a significantly higher CO 2 permeability than the other gases tested due to enhanced interactions with CO 2 as a result College of Material Science and Engineering, Guilin University of Technology, Guilin, China of Lewis acid-base interactions. Numerous studies have demonstrated that aromatic PIs with bulky -CF 3 groups, such as those produced from 4,4-(hexafluoroisopropylphenyl)dihydroanhydride (6FDA), have high gas separation properties, exceptional thermal stability and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic polyimides are known as one of the most potential gas separation materials because of their variable processability, remarkable mechanical performance, and outstanding thermal and chemical stability. In addition, the combination of dianhydride with diamine building blocks of the most varied chemical structures provides a great possibility to tune gas separation properties. However, compared with other polymers, traditional polyimides exhibit low permeability, which is related to their strong interchain interactions and high chain packing density.…”
Section: Introductionmentioning
confidence: 99%